Cerebral arterial and venous blood flow in adolescent multiple sclerosis patients and age‐matched controls using phase contrast MRI. Issue 2 (30th September 2013) - Macgowan, Christopher K.; Chan, Katherine Y.; Laughlin, Suzanne; Marrie, Ruth Ann; Banwell, Brenda
<x xml:space="preserve">Abstract</x> Purpose Altered cerebrovascular blood flow has been proposed as a mechanism for multiple sclerosis (MS). The primary objective of this study was to measure arterial and venous blood flow in adolescent MS patients and healthy controls (HC), in whom confounding factors such as age and lifestyle are less influential. Materials and Methods Phase‐contrast magnetic resonance imaging (MRI) was used to measure flow in 26 MS patients and 26 controls aged 17.7 ± 1.8 and 17.8 ± 2.1 years, respectively. Flow was measured in the left and right internal carotid arteries (ICA), vertebral arteries (VA), internal jugular veins (IJV), and epidural veins (EV). Eighteen MS patients returned for a second MRI examination after 6 months. In all participants, ultrasound criteria for chronic cerebrospinal venous insufficiency (CCSVI) were also evaluated. Results Flows (mL/min) in the MS group versus HC group were as follows: right ICA = 262 ± 57 vs. 263 ± 32, left ICA = 260 ± 67 vs. 270 ± 36, right VA = 96 ± 50 vs. 103 ± 30, left VA = 104 ± 37 vs. 118 ± 41, right IJV = 342 ± 180 vs. 345 ± 195, left IJV = 190 ± 131 vs. 250 ± 148, right EV = 33 ± 29 vs. 48 ± 43, and left EV = 36 ± 35 vs. 44 ± 28 (P > 0.17 for all comparisons). In MS participants, a nonsignificant trend to lower flow in the left IJV was observed, and the flow pulsatility index in the epidural veins was higher. Two MS participants met ultrasound criteria for CCSVI, but no significant difference in flow was detected. Conclusion No population difference in flow rate was detected in adolescent MS participants relative to age‐matched controls. J. Magn. Reson. Imaging 2014;40:341–347. © 2013 Wiley Periodicals, Inc.